Advances in the applications of biologics in the treatment of chronic spontaneous urticaria - Xuemei HUANG; Shanshan OU; Jiaoquan CHEN; Hui ZOU; Ziyan CHEN; Weihong WU; Hui WU; Runxiang LI; Huilan ZHU (Pifu-xingbing zhenliaoxue zazhi, 2024)
Chronic spontaneous urticaria (CSU) is a common immune skin disease in clinic. Mast cells are the key effector cells in the pathogenesis of CSU. With the continuous understanding of the pathogenesis of CSU in recent years, many new biologics have been used to treat CSU. Biologics can effectively treat CSU by targeting different stages of mast cell activation, blocking their activation and degranulation. According to the target and mechanisms of their action, biologics can be classified into inhibition of mast cell activation and intracellular signaling transduction, and activation of inhibitory receptor. This article will review the applications of biologics in the treatment of CSU.